(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The aim of the present investigation was to develop floating matrix tablets of stavudine to achieve prolong gastric residence time, leading to an increase in drug bioavailability and patient compliance. Floating tablets were prepared by wet granulation technique, using hydroxypropyl methylcellulose (HPMC K15M) as synthetic, pullulan gum as natural rate controlling polymers and optimum amounts of sodium-bicarbonate and citric acid as gas generating agents in suitable ratios to generate optimum buoyancy. Developed formulations were evaluated for weight variation, thickness, hardness, friability, drug content, in vitro drug release, floating lag time and floating buoyancy. All the formulations exhibited acceptable physical properties and the best formulation (F3) was selected based on in vitro characteristics. Further, the optimized formulation was evaluated for in vivo radiographic studies by incorporating BaSO4 as radio opaque substance. All the formulations were studied for in vitro drug release characteristics for 16 h. Optimized formulation showed controlled and prolonged drug release profiles while floating over the dissolution medium. Diffusion followed by erosion drug release mechanism was observed for the formulation, indicating that water diffusion and polymer erosion played an essential role in drug release. In vivo radiographic studies revealed that the tablets remained in the stomach for 8 ± 0.5 h in fasting human volunteers and indicated that gastric retention time was increased by the floating principle, which was considered and desirable for absorption window drugs.